PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR DAN KREATIFITAS SISWA KELAS III SD NEGERI SIDOREJO LOR 01 SALATIGA - Andita Putri Surya; Stefanus C Relmasira; Agustina Tyas Asri Hardini (Jurnal Pesona Dasar, 2018)
This research was conducted to improve learning result and creativity of third grade students of SD NegeriSidorejoLor 01 Salatiga in the third semester in Theme 6 Subtema 2 and 3 by applying the Learning Based Learning (PjBL) model. This study is a classroom action research (PTK) consisting of two cycles. Each cycle consists of two meetings, each of which consists of action planning, action implementation, observation and reflection and 1 evaluation meeting. Data obtained in this study were obtained from observation, document study, test. Data analysis technique used is descriptive quantitative and qualitative. The results showed that the application of learning model of Project Based Learning (PjBL) can improve student learning outcomes and creativity of third grstudents at SD NegeriSidorejoLor 01 Salatiga. At the pre cycle cycle percentage of student learning 46% and then increased in the first cycle as much as 72% and increased again to 92% in cycle II. While the creativity of students in the pre cycle of 29% increased to 51% in the first cycle of meeting 2 and increased to 90% in the second cycle of meeting 2.